Socioeconomic and cultural influence on preschoolers' play - Pfeifer, Luzia Iara; Rombe, Patrícia Gonçalves; Santos, Jair Licio Ferreira (Paidéia (Ribeirão Preto), 2009)
Assuming that the economic context influences children's play, this study aimed to examine the differences between toys used by children from two different socio-economic classes. Data collection was carried out with 50 mothers of children from three to six years old. According to Critério Brasil, half of the participants belonged to economic level A2 (Group 2) and the other half to economic level D (Group 1). Results indicate that there are significant differences between the use of computers (p=0.000), board games (p=0.023), games of arm (p=0.042), button soccer (p=0.012), more used by Group 2 and the use of clockwork toys (p=0.005), scrap toys (p=0.000) and jump rope (p=0.021), which were more present in Group 1. Results suggest that socioeconomic levels influence playing behaviors of preschooler children.